IMPLEMENTASI PEMBELAJARAN KITAB KUNING MELALUI MODEL PEMBELAJARAN FLIPPED CLASSROOM - Mu’alim Wijaya; Nafilatul Hasanah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
In this study explaining the implementation of yellow book learning based on flipped classroom in the Islamic boarding school of Nurul jadid, Zaid bin Tsabit (K) daughter. This research was motivated by the ineffectiveness of santri when studying the Book of Yellow. After being studied more deeply, it turned out that the main factor that caused this was because the learning model carried out by Ustadz was still classic, namely using the lecture model, as a result many santri were sleepy during activities. Therefore, researchers tried using a new learning model, namely the flipped classroom model. This research is a qualitative research carried out in the nurul jadid Islamic boarding school in the zaid bin tsabit (k) region of women, especially the class members of the Takhossus Diny Institute with a sample of 17 people. Flipped classroom is a learning model that is slightly different from the usual, that is before conducting the learning process in the class of students / students learn the subject matter in advance, and teaching and learning activities in the classroom are filled with work and discussing material or problems that students have not understood. Data collection methods in this study include: observation, interviews and documentation.